2020
DOI: 10.1177/1028315320932319
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Internationalization of Zimbabwe’s Higher Education Institutions Through a Decolonial Lens: Postcolonial Continuities and Disruptions

Abstract: Looking through the history of higher education in Zimbabwe, we argue that the concept of internationalization of higher education is not new to Zimbabwe. Understandings, manifestations, and processes of the phenomenon over time are examined to reveal the nuances of the internationalization process in its current mode of occurrence, in an attempt to not only understand it in its colonial and postcolonial manifestation but to situate it within a wider decolonial project. Using a decolonial lens, this article ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Although no participants openly criticised Vietnamese education, none of them spoke highly or described Vietnamese education in positive light. This finding supports that of Thondhlana, Abdulrahman, Chiyevo Garwe, and McGrath (2020) that colonialism still operates on contemporary beings and the impacts of colonisation is maintained in our self-image (Maldonado-Torres, 2007).…”
Section: Embrace Of Western Educationsupporting
confidence: 86%
See 1 more Smart Citation
“…Although no participants openly criticised Vietnamese education, none of them spoke highly or described Vietnamese education in positive light. This finding supports that of Thondhlana, Abdulrahman, Chiyevo Garwe, and McGrath (2020) that colonialism still operates on contemporary beings and the impacts of colonisation is maintained in our self-image (Maldonado-Torres, 2007).…”
Section: Embrace Of Western Educationsupporting
confidence: 86%
“…Furthermore, similar to the findings of Boussebaa and Brown (2017), public universities in my study acted as a system of control through organisational practices of rewarding or punishing the (non)conformers. Additionally, like participants of other research on HEIs in postcolonial contexts (Thondhlana et al, 2020), my participants were unreflexive of the legitimation of research outputs including publishing in international journals as a criterion for academic performance and promotion. This finding demonstrates the continuity of the "unequal relations of power" (Buckner & Stein, 2020, p. 151) between the Western practices and the postcolonial contexts' practices found in other research (Adebisi, 2016;Mullen, 2020;Sinha & Bathini, 2019).…”
Section: Mimicking Of Western Academia's Work Structures Around Resea...mentioning
confidence: 96%
“…The major contribution of this study was to address a well-acknowledged gap in literature relating to limited documentation on internationalization policy development methodologies (Thondhlana et al, 2020) and frameworks (Gornitzka et al, 2003). The ToC emerged as a critical step in the policy development process as stakeholder develop clear strategies in order to chart the way toward a common goal.…”
Section: Discussionmentioning
confidence: 99%
“…Cr aciun ( 2018) called for research that digs deeper into the rationales, approaches and processes used for internationalization policy development. Thondhlana et al (2020) found that, in countries where national internationalization policies exist, they rarely mention the policy development processes and imperatives. Furthermore, Gornitzka et al (2003) noted that internationalization research is largely descriptive and thin on conceptualizations of policy frameworks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation